Synthesis, spectroscopic studies, and antioxidant activities of novel thio/carbohydrazones and bis-isatin derivatives from terephthalaldehyde - MUĞLU, Halit; YAKAN, Hasan; BAKIR, Temel Kan (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2020)
New bis(isatins-thio/carbohydrazones) based on Schiff bases were prepared from terephthalaldehyde biscarbohydrazone and 5-substituted isatins in the presence of a drop of sulfuric acid under reflux in ethanol. Terephthalaldehyde bis(thio/carbohydrazone) was synthesized by the reaction of (thio)/carbohydrazide and terephthalaldehyde in the presence of a few drops of acetic acid under reflux in ethanol. The structures of these synthesized compounds were determined using IR, 1H NMR, and 13C NMR spectroscopy and elemental analysis. The in vitro antioxidant activity of all the compounds was determined by the 1,1-diphenyl-2-picryl hydrazyl (DPPH.) free radical scavenging method. Compound 2 showed the best antioxidant activity.
Keywords: Isatin; spectroscopic techniques; carbohydrazone; Schiff bases; Article; DPPH